Sistem Pendukung Keputusan Rekomendasi Aplikasi Editing Foto Dengan Menerapkan Metode MAUT Dan Pembobotan ROC - Advent Halawa; Agus Minta Riang Zega; Enzel Febrianti Telaumbanua; Muhammad Syahrizal (STMIK Budi Darma, 2022)
The Photo Editing application is an application that provides various features that are used to create various photos. There are many Photo Editing applications circulating in the play store, so in this case a Decision Support System (DSS) is needed in determining which Novel reading applications must be recommended to the general public. In determining this, there are several alternatives and criteria including rating, number of users, features, user reviews and paid features. A system supporting decision is needed in determining which Photo Editing application is worthy of being recommended with a combination of the ROC (Rank order Centroid) method and generating weight values on certain criteria and the MAUT (Multi-Attribute Utility Theory) method producing the best preferences according to data such as alternatives and criteria that have been determined and produce the best preference value in the 1st alternative, namely Picsart with a value of 0.649.